2020
DOI: 10.1194/jlr.ra120000869
|View full text |Cite
|
Sign up to set email alerts
|

SCD1 promotes lipid mobilization in subcutaneous white adipose tissue

Abstract: Beiging of white adipose tissue has beneficial effects on metabolism. Although it is known that beige adipocytes are active in lipid catabolism and thermogenesis, how it is regulated deserve more explorations. In this study, we demonstrate that stearoyl-CoA desaturase 1 (SCD1) in subcutaneous white adipose tissue (scWAT) responded to cold stimulation and was able to promote mobilization of triglyceride. In vitro studies showed that SCD1 promoted lipolysis in C3H10T1/2 white adipocytes. The lipolytic effect was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
(60 reference statements)
3
23
0
Order By: Relevance
“…A recent publication in our laboratory showed that BMP4 transcriptionally activates SCD1, an enzyme catalyzing the biosynthesis of unsaturated fatty acids. SCD1 promotes lipolysis and fat mobilization, which is fulfilled by the intermediate oleic acid ( 207 ). In fact, SCD1 accelerates both the synthesis and lysis of triglycerides, forming a somewhat futile cycle ( Fig.…”
Section: Bmp Signaling Participates In Multiple Processes Involving the Plasticity Of Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication in our laboratory showed that BMP4 transcriptionally activates SCD1, an enzyme catalyzing the biosynthesis of unsaturated fatty acids. SCD1 promotes lipolysis and fat mobilization, which is fulfilled by the intermediate oleic acid ( 207 ). In fact, SCD1 accelerates both the synthesis and lysis of triglycerides, forming a somewhat futile cycle ( Fig.…”
Section: Bmp Signaling Participates In Multiple Processes Involving the Plasticity Of Adipose Tissuementioning
confidence: 99%
“…In fact, SCD1 accelerates both the synthesis and lysis of triglycerides, forming a somewhat futile cycle ( Fig. 4 ) ( 207 ). We posit that this futile cycle driven by SCD1 may prime lipids in an active state ready for both incorporation and release of fatty acid and thus quickly respond to stimulation inducing energy consumption or storage, such as fasting/feeding or cold/heat exposure.…”
Section: Bmp Signaling Participates In Multiple Processes Involving the Plasticity Of Adipose Tissuementioning
confidence: 99%
“…In vivo and in vitro studies have shown that in adipose tissue SCD1 is involved in the promotion of lipid mobilization by enhancing lipolysis and lipogenesis [ 21 , 22 ]. SCD1 is a key enzyme involved in de novo lipogenesis and is responsible for the conversion of SFAs to MUFAs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SCD1 knockdown inhibited lipolysis in adipocytes by down-regulating lipases and reducing lipophagy. BMP4 was also demonstrated to be a crucial factor regulating SCD1 expression, up-regulating SCD1 expression through the Smad pathway [27].…”
Section: Discussionmentioning
confidence: 99%